1996
DOI: 10.1073/pnas.93.15.7944
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mucosal immune responses against a heterologous antigen fused to filamentous hemagglutinin after intranasal immunization with recombinant Bordetella pertussis.

Abstract: Live vaccine vectors are usually very effective and generally elicit immune responses of higher magnitude and longer duration than nonliving vectors. Consequently, much attention has been turned to the engineering of oral pathogens for the delivery of foreign antigens to the gutassociated lymphoid tissues. However, no bacterial vector has yet been designed to specifically take advantage of the nasal route of mucosal vaccination. Herein we describe a genetic system for the expression of heterologous antigens fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
2
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 42 publications
6
41
2
1
Order By: Relevance
“…However, there was little systemic IgA response detected, as has been observed in some other immunization studies (64). The induction of secretory IgA in the lung is required for immunological protection in some model systems (65), but not in others (66).…”
Section: Discussionmentioning
confidence: 83%
“…However, there was little systemic IgA response detected, as has been observed in some other immunization studies (64). The induction of secretory IgA in the lung is required for immunological protection in some model systems (65), but not in others (66).…”
Section: Discussionmentioning
confidence: 83%
“…In addition, attenuated B. pertussis is particularly well adapted for the nasal delivery of heterologous vaccine antigens and represents an attractive mucosal vaccine delivery system (2,10,20,34,38,39). Constructing BPZE1 derivatives producing viral antigens, thereby combining anti-inflammatory properties with the ability to induce adaptive anti-influenza virus immune responses, may thus constitute an interesting strategy for future development.…”
mentioning
confidence: 99%
“…Previous studies have shown that the highly efficient secretion mechanism of FHA can be used to present heterologous antigens by B. pertussis (38). Subsequently, we have found that a truncated derivative of FHA, named Fha44, that contains the N-proximal secretion determinants (16) was secreted even more efficiently than was full-length FHA (37).…”
Section: Resultsmentioning
confidence: 86%
“…However, efficacious mucosal vaccination generally requires multiple high-dose regimens (47). We have recently developed recombinant Bordetella pertussis strains able to induce mucosal (38) and systemic (33) antibody responses against heterologous antigens after a single i.n. administration.…”
mentioning
confidence: 99%